2014
DOI: 10.5539/gjhs.v6n3p109
|View full text |Cite
|
Sign up to set email alerts
|

Being at Peace as an Important Factor in Acquiring Teaching Competency by Iranian Nurse Teachers: A Qualitative Study

Abstract: It is imperative to understand the factor that influence teaching competency. Therefore, it is necessary to study those that have an impact on the process of acquiring teaching competency. Competent nurse teachers have an important role in the achievement of nursing students and improving the quality of nursing education. However, few researches have focused specifically on the process of acquiring teaching competency in nurse teachers and its related factors. This study as a part of more extensive research ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…In Iran undergraduate nursing students should pass 135 units including 26 basic sciences course units, 20 general course units, and 89 specialized course units for getting bachelor’s degree ( Borhani et al, 2010 ). In this regard, most of the Iranian nurse teachers have a Master’s degree or PhD in nursing ( Emamzadeh Ghasemi et al, 2014 ). Also, the role of Iranian nurse teachers has been highlighted as his/her effectiveness is thought to be dependent on the ability to have an effective relationship with nursing students.…”
Section: Introductionmentioning
confidence: 99%
“…In Iran undergraduate nursing students should pass 135 units including 26 basic sciences course units, 20 general course units, and 89 specialized course units for getting bachelor’s degree ( Borhani et al, 2010 ). In this regard, most of the Iranian nurse teachers have a Master’s degree or PhD in nursing ( Emamzadeh Ghasemi et al, 2014 ). Also, the role of Iranian nurse teachers has been highlighted as his/her effectiveness is thought to be dependent on the ability to have an effective relationship with nursing students.…”
Section: Introductionmentioning
confidence: 99%
“…Instructors’ competence and proficiency are largely dependent on the accurate performance evaluations that focus on improving their performance (Emamzadeh Ghasemi, Rafii, Farahani, & Mohammadi, 2014 ). Heshmati-Nabavi and Vanaki (2009) reported that incongruence between evaluation criteria and instructors’ competencies negatively affects their effectiveness and efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The reason may be related to the fact that these dimensions belong to the implicit part of the onion model, which is not convenient to measure and evaluate [ 14 ]. In the dimension of intrinsic motivation, experts believe that affinity motivation has a strong impact on the humanistic curriculum competence of undergraduate nursing teachers, with a weight of 0.6667 in this field, including gaining respect from others and a sense of belonging [ 38 ]. Therefore, creating a harmonious atmosphere has a good promoting effect on curriculum humanistic teaching.…”
Section: Discussionmentioning
confidence: 99%